REVALUASI (PENILAIAN KEMBALI) AKTIVA TETAP - Dul Mu'id (Jurnal Dinamika Ekonomi & Bisnis, 2005)
AbstractIn inflation, the enterprise must considere taking revaluation, it's caused the book value is not reflecting current market price. The requariment of enterprice taking revalaution are first payment of income taxes ten percent (I 0 %) on more market price minus book value. Assets revaluated was not moving for five years. If the assets move beforefive years. Second, thefinalty, the enterprise must pay twenty percent (20%) from residual of assets revaluation that payed income taxes, except moving to government for merger, accuation. Market price or par value isthe first  value after revaluation and that value uses  making  depresiation Key word : Revaluation, Assets, book value, market price, income taxes and depresiation.